INFLUENCE OF IN-SITU CONCRETE AND REINFORCING STEEL PROPERTIES ON THE SERVICEABILITY PERFORMANCE OF REINFORCED CONCRETE FRAMES - Priyono, Pujo; Fiendyo, Muhammad Haykal (Jurnal Pensil : Pendidikan Teknik Sipil, 2026)
This study evaluates the influence of differences between the in-situ concrete and reinforcing steel properties and their design values on the performance of a reinforced concrete frame structure, assessed in terms of strength and serviceability. A case study was conducted on the ASN Ministry of Finance apartment building in Denpasar through field material testing, element capacity evaluation, and structural modeling using SAP2000. The installed concrete exhibited an average compressive strength of 24.5–25.2 MPa with a deviation of 1.0–1.3% from the design value, remaining within standard tolerances. The reinforcing steel showed a higher yield strength than specified, increasing beam flexural capacity by approximately 3.3%, while the axial capacity of columns decreased by an average of 4.6%. Nevertheless, the column-to-beam capacity ratio satisfied the Strong Column Weak Beam requirement (1.48–2.00). Structural response analysis indicated that interstory drift and P–Delta effects were below allowable limits, demonstrating adequate lateral stiffness and stability. Overall, controlled variations in material properties did not reduce global structural performance but affected the safety margin. The findings highlight the importance of material quality control in ensuring the reliability of earthquake-resistant structures.